Co-employment of permanently and temporarily employed agents - Werner Güth; Martin G. Kocher; Vera Popova (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2010)
One-shot interaction and repeated interaction often co-exist in the real world. We study possible behavioral effects of this co-existence in a principal-agent setting, in which a principal simultaneously employs a permanent and a temporary agent. Our experimental results indicate that there is 'discrimination' between the two agents and that the available information for agents determines the extent of this discrimination, even though the theoretical solution of the game implies equal treatment of agents. Discrimination is, thus, a consequence of reciprocity. Agents that are discriminated against react negatively by withholding effort.
Keywords: C72; C91; D21; J31; 330; principal-agent problem; permanent and temporary employment; fairness; wage discrimination; Agency Theory; Befristeter Arbeitsvertrag; Arbeitsverhältnis; Gerechtigkeit; Lohndifferenzierung; Austauschtheorie; Test